A course‐based undergraduate research experience in biochemistry that is suitable for students with various levels of preparedness. Issue 3 (22nd February 2019) - Shelby, Shameka J.
Abstract: Due to resource limitations at predominantly undergraduate institutions, research opportunities for non‐senior students can be limited. To provide opportunities for a variety of students to gain exposure to research, a course‐based undergraduate research experience (CURE) was designed and conducted. Coupled inquiry was used to allow underclassmen and upperclassmen to participate. Students first utilized a bioinformatics approach to develop hypotheses concerning protein interactions with the receptor Mer tyrosine kinase (MERTK). Students designed experiments to identify specific sites of interactions with SH2‐domain proteins utilizing an assortment of basic biochemical techniques. The semester culminated in students testing their hypotheses and producing manuscripts. Underclassmen that participated in the course also benefitted from mentor–mentee relationships developed with upperclassmen due to the collaborative nature of the course. The structure of the course also allows for further studies to be conducted based on novel findings and is highly adaptable to receptor tyrosine kinases found in other tissue types. © 2019 International Union of Biochemistry and Molecular Biology, 47(3):220–227, 2019.